2020
DOI: 10.1002/csr.1931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental corporate social responsibility on green attitude and norm activation process for sustainable consumption: Airline versus restaurant

Abstract: The major aim of this research was to develop theoretical frameworks clearly explicating airline and restaurant customers' decision formation for eco‐friendly products. Using a quantitative approach, we successfully broadened the norm activation theory by integrating environmental corporate social responsibility (CSR) and attitude toward the behavior. In addition, the theory was effectively deepened by taking the influence of product type (airline vs. restaurant) into account. The developed conceptual framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 54 publications
1
58
0
6
Order By: Relevance
“…For example, the study confirmed that the most influential dimension of CSR to influence consumer loyalty is the social dimension (β = 0.242 **). These results are unlike the results of developed countries; for instance, in their recent study, Han et al [79] and Han, Yu, and Kim [37] mentioned that the environmental dimension of CSR has the most influence to induce consumer loyalty. However, in the South Asian region, especially from the perspective of Pakistan, this finding is meaningful because the concept of CSR is still in its infancy stage in Pakistan.…”
Section: Discussionmentioning
confidence: 59%
“…For example, the study confirmed that the most influential dimension of CSR to influence consumer loyalty is the social dimension (β = 0.242 **). These results are unlike the results of developed countries; for instance, in their recent study, Han et al [79] and Han, Yu, and Kim [37] mentioned that the environmental dimension of CSR has the most influence to induce consumer loyalty. However, in the South Asian region, especially from the perspective of Pakistan, this finding is meaningful because the concept of CSR is still in its infancy stage in Pakistan.…”
Section: Discussionmentioning
confidence: 59%
“…CSR is an instrument that needs to be utilized while searching for sustainability, and it can be seen as a valuable contribution to the sustainable destination development (Font & Lynes, 2018). The travel and tourism companies have responsibilities at the places they operate, which could prompt them to adopt CSR (Han et al, 2020). This study confirmed that the merits of CSR have been increasingly valued by the tourists, which calls for the travel and tourism companies to pay attention to the commercial mechanisms and the non-commercial mechanisms when facing business challenges in times of a pandemic and with a post-pandemic economic recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In the competitive market some of the firms take aggressive environmental efforts to ensure customer well-being as tool to retain and attract customers which eventually help build green image and green competitive advantage of the firm (Han, Yu, & Kim, 2019). Nowadays firms are increasingly implementing E-CSR to complement various brand loyalty game plans (Han, Chua, Ariza-Montes, & Untaru, 2020). If customers are convinced with the environmental concerns of the company, they most often evaluate the firm more positively by perceiving a connection between the firm and themselves (Fonseca & Ferro, 2015).…”
Section: Green Corporate Imagementioning
confidence: 99%